And then I go [videorecording (DVD)] - Darbo, Arman; Barth, Sawyer; Lynskey, Melanie; Shepard, Jim
In the cruel world of junior high, Edwin suffers in a state of anxiety and alienation alongside his only friend, Flake. Misunderstood by their families and demoralized at school daily, their fury simmers quietly until an idea for vengeance offers them a terrifying release.